The smallest coffins are the heaviest : understanding how bereaved parents in Singapore cope with the loss of their children with life-limiting illness - Nabilah Ahmad (2018)
As fittingly described by the adage “the smallest coffins are the heaviest”, the experience of having one’s child suffer from and succumb to a chronic life-limiting illness is filled with deep, intense emotions and a wide range of challenges. The present study aimed to explore the coping strategies and support systems that have helped bereaved parents of children with life-limiting illness in Singapore carry the weight of their loss. Meaning-oriented interviews were conducted with six family units. Thematic analysis revealed ten themes under three overarching categories presented in a systemic view. Parents bore the weight of the loss and coped through cognitive appraisal. This included developing an optimistic mindset, creating faith-driven meanings, finding balance amidst the chaos, developing continuing bonds, believing in their duty as a parent, as well as redirecting their focus. In addition, family and friends provided affective support by being involved in the experience together with them and by providing them with an outlet to express their feelings. Practical support also played a key role in their coping process, specifically work flexibility and pragmatic assistance provided by palliative care teams. These findings and their implications were discussed.